English English: English - May Su Hlaing; Tin Tin Hla (The Indonesian Journal of Computer Science, 2026)
DC-DC buck converters are widely employed in power electronic systems to provide efficient voltage regulation for various applications. However, the converter performance is significantly influenced by the duty cycle, which determines the output voltage and current characteristics. This study presents a comparative analysis of the voltage and current responses of a DC-DC buck converter operating at duty cycles of 0.5 and 0.25 using MATLAB/Simulink. The objective is to evaluate the effect of duty cycle variation on the converter's dynamic and steady-state performance. A simulation model was developed and tested under identical operating conditions, and the resulting output waveforms were analyzed. The results indicate that increasing the duty cycle enhances both the average output voltage and load current, while a lower duty cycle reduces the output magnitude. The simulated responses closely agree with the theoretical principles of buck converter operation, demonstrating the effectiveness of MATLAB/Simulink for performance evaluation and design optimization.